Cryopreservation as a Method to Preserve Some Fruit and Berry Crops and Wild Medicinal Plants - Pavlov, Alexander V.; Verzhuk, Vladimir G.; Orlova, Svetlana Yu.; Radchenko, Olga Ye.; Yerastenkova, Maria V.; Dodonova, Aleхandra Sh.; Gavrilkova, Yelena A.; Sitnikov, Maksim N.; Filipenko, Galina I.; Murashev, Sergey V. (Problems of Cryobiology and Cryomedicine, 2019)
The cryopreservation eﬀ ect on viability of black currant cuttings (Ribes nigrum L.), sweet cherry pollen (Cerasus avium L. Moench), Prunus rossica Erem. diploid plum and Prunus domestica L. garden plum pollen, as well as the seeds of wild medicinal plants: Syrian rue (Peganum harmala L.), tansy (Tanacetum ulutavicum Tzvel.) and sawwort (Serratula dissecta Ledeb.) was studied. The viability in 5 cultivars of R. nigrum L. was decreased after cryopreservation; in 7 cultivars of C. avium L. (17 cultivars totally) it was increased, in 6 cultivars there were no changes, in 4 ones it was decreased; in 3 varieties of P. rossica Erem. (9 cultivars totally) the one was increased, in 3 ones there were no changes, in 3 ones it decreased; in 6 cul-tivars of P. domestica L. (13 cultivars totally) this index was increased, in 3 ones there were no changes, in 4 ones it decreased; in P. harmala L. seeds it was unchanged; in the seeds of S. dissecta Ledeb. it was increased. For the seeds of three medicinal plants there were selected the optimal concentrations of cryoprotectants and thawing modes as follows: P. harmama L. – 100% glycerol, slow freeze-thawing; T. ulutavicum Tzvel. – 10% sucrose, slow warming; S. dissecta Ledeb. – 3% DMSO, rapid warming. Probl Cryobiol Cryomed 2019; 29(1): 044–057